2017
DOI: 10.1021/acs.langmuir.7b01799
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Spreading of Ionic Liquids on an Aqueous Substrate

Abstract: The spontaneous spreading of thin liquid films over substrate surfaces is attracting much attention due to its broad applications. Under particular conditions, surfactants deposited on substrates exhibit unstable spreading. In spite of the large effects of the stability of the spreading on the accuracy and efficiency of industrial processes that use the spreading, understanding how the stability of the spreading process is governed by the physical and chemical properties of the system is still little known. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although a definition and general properties can be ascribed to ILs, there are still some exceptions. Some ILs can be volatile, flammable, unstable, and even toxic [14,15]. In this regard, a wise choice of IL must be always considered by having in mind the desired application.…”
Section: Ionic Liquids Vs Deep Eutectic Solvents: Definition and Propertiesmentioning
confidence: 99%
“…Although a definition and general properties can be ascribed to ILs, there are still some exceptions. Some ILs can be volatile, flammable, unstable, and even toxic [14,15]. In this regard, a wise choice of IL must be always considered by having in mind the desired application.…”
Section: Ionic Liquids Vs Deep Eutectic Solvents: Definition and Propertiesmentioning
confidence: 99%
“…and organic cations (phosphonium, quaternary ammonium, imidazolium, etc. ). Compared with traditional solvents, ILs have the advantages of high heat resistance, wide variable viscosity range, low or even negligible vapor pressure, adjustable structure, low toxicity, and so forth. , Recent studies have shown that using a very small amount of ILs can achieve a high DNA extraction rate (97%) . Although ILs have high extraction efficiency, after DNA extraction, ILs are usually separated by extraction or distillation, which often leads to loss of ILs or incomplete separation.…”
Section: Introductionmentioning
confidence: 99%
“…and organic cations (phosphonium, quaternary ammonium, imidazolium, etc.). 11−13 Compared with traditional solvents, ILs have the advantages 14 of high heat resistance, wide variable viscosity range, low or even negligible vapor pressure, adjustable structure, low toxicity, and so forth. 15,16 Recent studies have shown that using a very small amount of ILs can achieve a high DNA extraction rate (97%).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous works indicated that the initial driving force for the wetting and spreading of an oil droplet on the air–water interface was dominated by the gravity force and balanced by the resistance from the viscous force. , With the progression of the spreading, the oil film became more and more thinner. The surface tension gradient replaced gravity gradually as the main spreading driving force, although the spreading resistance was still dominated by the viscous force. , Investigations on the spreading behavior of oil droplets driven by surface tension gradient have been conducted extensively. It was demonstrated that the Marangoni convection induced along the air–water interface had a significant impact on the spreading characteristics of the oil droplet and the stability of the thin oil film. The spreading stability of the oil film on the air–water interface depended closely on its rheological properties (viscosity and elasticity). However, most of the works on the spreading behavior driven by the Marangoni effect focused on the interfacial flow characteristics of the oil film and the formation mechanism of Marangoni convection along the gas–water interface. , Investigations were scarce into the change in the interface viscosity and elasticity that resulted from the chemical reaction-driven Marangoni convection and its effect on the spreading behavior and the stability of the organic oil film.…”
Section: Introductionmentioning
confidence: 99%